Dampak Sistem Informasi terhadap Organisasi Medan Membaca - Elfi Yanti Ritonga; Dewi Rahmadanti; Rizki Hajar; Nurhidayah Lubis; M Ridho Ar-Rasyid (Universitas Muhammadiyah Enrekang, 2022)
The existence of technology, such as the internet, gadgets, tablets, and others, seems to have begun to shift the role of libraries in this more modern era. Due to the widespread use of social media, libraries may have been forgotten by children or students. Even for reading, it takes a very long time to finish a book because it is so heavy. However, reading a few pages of reading available on HP will not be boring and can be finished immediately. Every culture has knowledge, science, and technology that is used to interpret, understand, and use the environment and its contents as well as a tool to utilize, process, and apply it to meet human needs. Technological advances are communicated very quickly. Society now has various facilities to perform daily tasks thanks to advances in science and technology. Today, almost everyone uses communication tools, as can be seen from the experience of today's youth. Adolescence is a period of transition from childhood to adulthood when people begin to be influenced by their environment and become more willing to become what they want to be. Adolescents engage in more intense self-seeking behavior as a result of advances in communication technology. The purpose of this paper is to define the function of information systems in an organization. Library research techniques are used in the writing process. From the discussion, it is clear that organizational information systems can never be fully or completely automated. However, if the appropriate overall strategy is developed by the relevant system employees and supported by adequate financial resources, a management information system is very feasible and practical. Cross-functional information systems that support the main goals of the organization must be maintained and developed continuously. A decision support system (DSS) that combines models, databases, and directly interacting managers serves the main functions of the organization.